PENJERAPAN LOGAM KADMIUM (Cd2+) DENGAN ADSORBEN CANGKANG TELUR BEBEK YANG TELAH DIAKTIVASI - Krisnawati, Jasinda, Iriany (Universitas Sumatera Utara, 2013)
Harzadous waste water is the waste that can be harmful to human’s health. One of heavy metals that contains in harzadous waste is cadmium. This research aims to investigate the characteristic of cadmium adsorption, equilibrium time, percentage adsorption, adsorption kinetic, adsorption isotherm and capacity of cadmium adsorption by using duck egg’s shell adsorbent. Duck egg’s shell adsorbent that had been activated at 600 oC were put into cadmium solution and mixed together. Every 10 minutes experimental samples were analyzed using AAS. The results indicated that percentage adsorption increases and the longer equilibrium time will be reached with an increase of adsorbent dosage. The Lagergen first order Models was applied as adsorption kinetics model and the Bangham Models was applied as adsorption isotherms models.